Avaliação dos efeitos da imersão diária em água termomineral de Caldas da Imperatriz-SC na inflamação periférica em camundongos - Madeira, Fernanda (2016)
Objective: This study aimed to evaluate the effects of daily immersion in thermomineral water from Caldas da Imperatriz-SC in a preclinical model of inflammatory pain. Methods: After approval of the protocol by the Ethics Committee on Animal Use UNISUL - CEUA / UNISUL (Protocol 13.0064.08.IV), male Swiss mice (25 to 35g) received an intraplantar injection of complete Freund's adjuvant (CFA). Twenty-four hours after the injection we initiated the immersion treatments with thermomineral water (ATM for ―água termomineral‖ in portuguese). 3, 10 or 30 minute treatments were performed six days a week for three weeks. Mechanical hyperalgesia and edema were evaluated. Additionally, at the end of first week after injection the concentrations of pro- and anti-inflammatory cytokines in the paw and spinal cord were determined. Results: Daily ATM immersion reduced the mechanical hyperalgesia in a dose dependent effect (corresponding to immersion time); Daily treatment with immersion in ATM induced a summed effect, which can be evidenced by the extension of the anti-hyperalgesic response in the time-course evaluations; daily immersion in ATM restored sensory response even after the end of the treatment; daily immersion in ATM did not affect paw edema. Furthermore, our findings indicate that immersion treatment reduced hyperalgesia through a reduction of pro-inflammatory cytokines and concomitant increase of antiinflammatory cytokine concentration in animal’s paws; in association with a decrease of pro-inflammatory cytokines spinal cord concentration. Conclusion: This study provides evidence that BT (balneotherapy) carried out with ATM from Santo Amaro da Imperatriz, SC reduces inflammatory mechanical hyperalgesia, but does not decrease edema in an animal model of persistent peripheral inflammatory pain.